Complete nucleotide sequence of a 16S ribosomal RNA gene from Escherichia coli. - Brosius, J (1978)
The complete nucleotide sequence of the 16S RNA gene from the rrnB cistron of Escherichia coli has been determined by using three rapid DNA sequencing methods. Nearly all of the structure has been confirmed by two to six independent sequence determinations on both DNA strands. The length of the 16S rRNA chain inferred from the DNA sequence is 1541 nucleotides, in close agreement with previous estimates. We note discrepancies between this sequence and the most recent version of it reported from direct RNA sequencing [Ehresmann, C., Stiegler, P., Carbon, P. & Ebel, J.P. (1977) FEBS Lett. 84, 337-341]. A few of these may be explained by heterogeneity among 16S rRNA sequences from different cistrons. No nucleotide sequences were found in the 16S rRNA gene that cannot be reconciled with RNase digestion products of mature 16S rRNA.